If I ran the zoo - Seuss, Dr. (New York : Random House, 1977)
If Gerald McGrew ran the zoo, he'd let all the animals go and fill it with more unusual beasts--a ten-footed lion, an Elephant-Cat, a Mulligatawny, a Tufted Mazurka, and others.
Keywords: Stories in rhyme; Fantasy; Zoos -- Juvenile fiction; Stories in rhyme